Effect of spudcan shape on mitigating punch-through in sand-over-clay. Issue 3 (8th March 2019) - Lee, Joonmo; Hossain, Muhammad Shazzad; Hu, Pan; Kim, Youngho; Cassidy, Mark J.; Hu, Yuxia; Park, Sunggun
Abstract : Spudcan punch-through in layered seabed sediments is one of the major concerns for the jack-up industry. This paper reports the results from a series of centrifuge model tests undertaken to assess the effect of various shapes of spudcan base at mitigating punch-through in sand-over-clay deposits. The experimental programme was carried out in a drum centrifuge by varying the spudcan base profile, skirt length on the periphery and number of holes through the spudcan. The large testing area of one soil sample prepared along the full drum channel enabled an extensive number of 13 spudcan penetration tests under consistent soil conditions. Additional large-deformation finite-element analyses were carried out to explore the soil failure mechanisms around each spudcan with different shapes. The spudcan base profile and number of holes through the spudcan showed no apparent influence on the spudcan penetration behaviours, as the sand blocked the spudcan holes during penetration. Only the skirt showed a positive influence at mitigating punch-through. The positive influence was greater with a longer skirt.